Attitudes toward COVID-19 vaccination in the nursing profession: validation of the Italian version of the VAX scale and descriptive study - Tomietto, M.; Comparcini, D.; Simonetti, V.; Papappicco, C. A. M.; Stefanizzi, P.; Mercuri, M.; Cicolini, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Foreward. Nurses’ attitudes towards COVID-19 vaccination is a relevant issue, for the protection of the vulnerable people they care for, and the key role they play in promoting health behaviors that encourage trust and adherence to vaccination among population. This study aimed to validate the Italian version of the Vaccination Attitudes Examination (VAX) scale and to describe nurses’ attitudes towards COVID-19 vaccination.Design. A cross-sectional study was carried out from May to June 2021. Descriptive statistics, Explorative and Confirmatory Factor Analyses have been performed.Methods. An online survey was carried out in Italy. The VAX scale referring to the COVID-19 vaccine was used. Findings. 430 nurses participated in the study, mainly female (73.2%). Mean age was 40.2 years. VAX scale revealed an optimal reliability; Exploratory Factor Analysis and Confirmatory Analysis supported a 4-factors model. VAX scale mean scores showed low mistrust about vaccine’s benefit (2.03±1.07), concerns about commercial profiteering (2.33±1.39) and preference for natural immunity (2.90±1.37). More worries concerning unexpected future effects were found (4.46±1.36). Gender, taking care of a frail person in family, having children or working in a COVID-19 setting are no significantly related to vaccination attitude. Participants from northern Italy expressed greater confidence in vaccine’s benefits, the younger had significant lower scores about commercial profiteering. Conclusions. The Italian version of the VAX scale resulted a reliable tool to assess the nurses’ attitudes towards COVID-19 vaccination. An overall positive nurses’ attitude towards the COVID-19 vaccination was highlighted. The concern about unforeseen future effects suggested the need to increase the information on this issue. Clinical relevance. The results provided a valid and reliable tool to measure vaccination attitudes in the Italian context. This study could strengthen the health policies with educational interventions of healthcare workers through specific vaccination pathways. The healthcare professionals’ vaccination attitudes play the key role also in promoting vaccination uptake in the population.